Advanced approach to primary microsurgical debridement of extensive scleral lacerations involving simultaneous vitrectomy and chorioretinal wound closure - S.S. Shamkin; S.N. Subbotina; A.B. Stepanyants; D.V. Salov (РМЖ "Клиническая офтальмология")
S.S. Shamkin1, S.N. Subbotina1, A.B. Stepanyants2, D.V. Salov2 1Central City Clinical Hospital № 23, Yekaterinburg, Russian Federation 2Ural State Medical University, Yekaterinburg, Russian Federation Background: the current strategy for managing extensive zone 3 scleral lacerations implies delayed subtotal vitrectomy. A high rate of poor treatment outcomes requires novel approaches to surgical debridement of lacerations given anatomical and pathogenic specifics. Aim: to assess the treatment results of extensive zone 3 scleral laceration surgery by simultaneous vitrectomy and chorioretinal wound debridement. Patients and Methods: 14 patients (14 eyes) diagnosed with extensive penetrating scleral/corneoscleral laceration and polymorphic intraocular lesions associated with grade 4–5 visual impairment were enrolled. All patients underwent primary microsurgical debridement using a technique that involved external debridement and suturing of scleral laceration, single-step subtotal vitrectomy, and internal debridement of the chorioretinal wound. The chorioretinal wound was filled with pure platelet-rich plasma (P-PRP). Endotamponade was performed using silicone oil (n=9) or air-gas mixture (n=5). Results: after 6 months, visual acuity (VA) was estimated to be 0.02–0.5 in 12 patients and light perception in 2 patients. During the follow-up, no phthisis bulbi was reported. The progression of proliferative vitreoretinopathy (formation of intraretinal adhesions or subretinal bands involving healthy retina) was reported in 3 patients (21.4%). Chorioretinal scars were characterized by local nonaggressive proliferation, no prominence in the vitreous cavity, or proliferation of tissue beyond the scars. Conclusion: our approach to severe eye injury management has demonstrated positive outcomes by providing a stable anatomical result, significant improvement in early and late postoperative VA. Keywords: open globe injury, primary microsurgical debridement, proliferative vitreoretinopathy, scleral lacerations, vitrectomy, platelet-rich plasma. For citation: Shamkin S.S., Subbotina S.N., Stepanyants A.B., Salov D.V. Advanced approach to primary microsurgical debridement of extensive scleral lacerations involving simultaneous vitrectomy and chorioretinal wound closure. Russian Journal of Clinical Ophthalmology. 2023;23(3):124–128 (in Russ.). DOI: 10.32364/2311-7729-2023-23-3-3.